Expresión génica y proteica de las colinesterasas en tejido hepático humano y células HepG2 - Pérez Aguilar, Benjamín (Universidad Autónoma Metropolitana, 2011)
INTRODUCTION. Hepatocellular carcinoma is one of the most common malignancies in the world, being the fifth most common cancer in men and the eighth in women. In Mexico, incidence is lower at 3.3 cases per 100,000 habitants, making it essential to continue the analysis of molecular changes present in this type of cancer. In recent years, has been reported that the enzymatic activity of acetilcolinestesa (AChE) is decreased in some tumors. Although there is no known biological function of butyrylcholinesterase (BuChE), it appears that performs functions of detoxification. The participation of these enzymes in malignancies is unknown, there is a notable relationship between low enzyme activity and cancer. The AChE gene undergoes a process of three cutting-mRNA alternative splicing generating: AChE-T (nervous system and muscle cells), AChE-H (red blood cells and lymphocytes), and AChE-R (pathological conditions). All AChE variants hydrolyze acetylcholine (ACh) on nerve transmission and the neuromuscular junction. BuChE gene does not undergo by alternative splicing, and it is preferentially expressed on liver. The activity of both cholinesterases depends on proper post-translational glycosylation. METHODOLOGY. Healthy liver samples were determined by a histopathological analysis and the cell line HepG2 was propagated in suitable conditions of cultivation. AChE and BuChE activities were solubilized from healthy human liver hepatoblastoma cells (HepG2) using Hepes-saline buffer with and without Brij-97 in a ratio 1:10 (P / V). Enzyme activity was estimated by the Ellman method and the total protein content by Bradford method. RNA extraction was performed by the Trizol method and RT-PCR amplification of two steps using specific primers for AChE (H, T and R) and BuChE. The post- translational processing was studied in the supernatants of dissolution, which began to interact with lectins of different,specificity. RESULTS AND CONCLUSIONS. The healthy human liver HepG2 cells synthesize AChE and BuChE, whose activities were lower on HepG2 when compared of those found on healthy liver cells. This, suggests AChE and BuChE roll on cellular transformation. The human liver and HepG2 cells both expressed the three mRNA variants. Both human liver and HepG2 cells expressed BuChE transcript. Lectins interaction with solubilized cholinesterases showed that post-translational processing was abnormal on HepG2 cells, which apparently has an impact on the low enzyme activity. This shows the relevance of the level of process quality control of both enzymes, or its relationship to alterations in specific glycosyltransferases.; INTRODUCCIÓN. El carcinoma hepatocelular es uno de los tumores malignos más comunes en el mundo, siendo el quinto cáncer más frecuente en hombres y el octavo en mujeres. En México, la incidencia es menor a 3.3 casos por cada 100,000 habitantes, por lo que es indispensable continuar el análisis de cambios moleculares presentes en éste tipo de cáncer. En los últimos años, se ha reportado que la actividad enzimática de la acetilcolinestesa (AChE) se encuentra disminuida en algunas neoplasias. Aunque no se conoce la función biológica específica de la butirilcolinesterasa (BuChE), esta cumple funciones de desintoxicación. La participación de estas enzimas en los procesos cancerosos se desconoce, pero parece existir una relación entre una baja actividad enzimática y el cáncer. El gen de AChE sufre un proceso de corteempalme alternativo generando tres mRNAs; AChE-T (sistema nervioso y células musculares), AChE-H (eritrocitos y linfocitos), y AChE-R (estados patológicos). Todas las variantes proteicas hidrolizan acetilcolina (ACh) durante la transmisión nerviosa y la unión neuromuscular. El gen de la BuChE no sufre corte-empalme alternativo, expresado en hígado preferentemente. La actividad de ambas colinesterasas depende de una adecuada glicosilación post-traduccional. METODOLOGÍA. Las muestras de hígado sano se determinaron por un análisis histopatológico y la línea celular HepG2 se propago en condiciones adecuadas de cultivo. Las actividades AChE y BuChE se solubilizaron de hígado humano sano y las células de hepatoblastoma (HepG2) usando amortiguador Hepes-salino sin y con Brij-97 en una relación 1:10 (P/V). La actividad enzimática se estimó por el método de Ellman y el contenido de proteína total por el procedimiento propuesto por Bradford. La extracción de RNA se realizó por el método de Trizol y la amplificación por RT-PCR de dos pasos, usando cebadores específicos para AChE (H, T y R) y BuChE. El procesamiento post-traduccional se estudió con los sobrenadantes de la solubilización, los que se pusieron a interactuar con lectinas de distinta especificidad. RESULTADOS Y CONCLUSIONES. El hígado humano sano y las células HepG2 sintetizan AChE y BuChE, cuyas actividades fueron menores en HepG2 respecto al hígado sano. Lo anterior, hace suponer la participación de AChE y BuChE en la transformación celular. El hígado humano y las células HepG2 expresaron las tres variantes de RNAm de AChE. Tanto el hígado humano como las células HepG2 expresaron el transcrito de BuChE. La interacción de lectinas con las colinesterasas solubilizadas mostró que el procesamiento post-traduccional fue anómalo en las células HepG2; lo que al parecer tiene repercusión en la baja actividad enzimática. Lo anterior, muestra la relevancia del nivel del proceso de control de calidad de ambas enzimas, o su relación con alteraciones en las glicosiltransferasas específicas.